Facilitating positive attitude in students: A study of critical e-learning factors - Verma, Iti; Nigam, Shalini (Indian Journal of Educational Technology, 2024)
Planning the implementation of e-learning requires study of various factors that play a key role in its success. Although many studies on e-learning factors have been conducted from time to time, the majority of them aimed at identifying critical success factors based on literature review or through surveys, while only a few studied the impact of critical success factors on other variables. (Farid et al., 2018; Qammach and Al-Sharifi, 2021). The present study aims to analyze the impact of critical success factors on students’ attitudes towards e-learning. Through the questionnaire, a total of 300 respondents were reached, out of which 221 responded giving a response rate of 74 per cent. Analysis of data was done using IBM SPSS and AMOS graphics. Findings reveal that University Support has a positive impact on students’ attitudes towards online learning, whereas, technology issues have a negative impact on students’ attitudes towards e-learning. Instructor support is seen to have an insignificant impact on students’ attitudes towards e-learning. Only three critical factors have been tested in the present study to study their impact on students’ attitudes, while future studies can involve even more factors. The study holds importance for all stakeholders in the education industry.